Development of a rowing-specific Vo2max field test - Huntsman, H. D.; DiPietro, L.; Drury, D. G.; Miller, T. A. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to develop an aerobic capacity test for rowers using minimal equipment that could be used in the field. Thirty rowers (15 men and 15 women) between the ages of 18 and 26 years were recruited on a volunteer basis from the District of Columbia metro area. The testing protocol consisted of a maximum of 7 2-minute stages on a rowing ergometer, separated by 30-second breaks where lactic acid concentrations were analyzed. Starting intensity for men was 200 W, although women started at 150 W, and each stage increased by 50 W. Expired gasses were collected during the test, and athletes were asked to row until maximal volition so that the directly measured Vo2max could be compared to predicted values. Peak heart rates from each completed stage were plotted, and regression equations were calculated to predict Vo2max. Separate regression equations were calculated for men and women. The predicted Vo2max values were approximately 23 and 25% lower than what was actually achieved for men and women, respectively. Heart rate was a stronger correlate of Vo2max in men compared with in women. Among men, we observed a moderate and statistically significant correlation (r = 0.55; p = 0.05), whereas among women, no such agreement was observed (r = -0.05; p > 0.85). The principle finding of this study was that the test was adequate in predicting Vo2max in men but was inadequate in its prediction in women. With slight modifications to the testing protocol, stronger correlations and a more accurate prediction of Vo2max is expected in men.